THE EFFECT OF USING REALIA OBJECTS TOWARD STUDENTS’ ACHIEVEMENT IN WRITING DESCRIPTIVE TEXT AT THE TENTH GRADE OF SMK NEGERI 1 TAMBUSAI UTARA - Mustika, Sri; Donal, Andri; Husni, Rijalul (JEE (Journal of English Education), 2018)
The aim of this research was to examine the effect of using realia objects toward students’ achievement in writing descriptive text at tenth grade of SMK N 1 Tambusai Utara. The design of this research was quasi experimental research design. The research used cluster sampling with 32 students as participants for both of experimental and control classes. SPSS was used to analyze the data. After analyzing the data by using independent sample t-test, the data showed that there was a significant effect in post-test score between experimental and control classes. The mean score in experimental class was 51.3031 with the standard deviation was 6.46. Meanwhile in control class the mean of post-test score was 39.617, and standard deviation was 6.67319. With df both of two classes was 30, and t-value was 5.184 with p-value 0.000 compared with t-table 5% (0.05) = 1697 and 1% (0.01) = 2457. The data shows that t-value of 5.184 > t-table 5% = 1697 and 1% = 2457. Thus the alternative hypothesis (Ha) was accepted, and null hypothesis (Ho) was rejected. Thus, it can be concluded that there was a significant effect of using realia objects toward students’ achievement in writing descriptive text at the tenth grade of SMK N1 Tambusai Utara.